'We need to remember they died for us': How young people in New Zealand make meaning of war remembrance and commemoration of the First World War. (1st July 2017) - Sheehan, Mark; Davison, Martyn
Abstract : This article examines the extent to which young people in New Zealand share the dominant beliefs and assumptions that inform contemporary notions of war remembrance concerning the First World War. In particular, it considers how they make meaning of the ANZAC/Gallipoli narrative. Informed by two empirical studies, it questions whether young people uncritically accept the dominant cultural memory messages about the First World War that shape commemorative activities or whether they share a wider range of perspectives on war remembrance. While the purpose of commemorative activities is to convey particular memory messages about appropriate ways to remember the First World War, young people are not passive in this process. Although they typically do not demonstrate a firm grasp of all the relevant historical details about the First World War, when given the opportunity to do so they appear to be engaging critically with the production of cultural memory messages about war remembrance.